When Participants Do Not Agree: Member Checking and Challenges to Epistemic Authority in Participatory Research. Issue 4 (November 2019) - Caretta, Martina Angela; Pérez, María Alejandra
Transactional validity, a common approach in participatory research, is attained when preliminary analyses of research results are discussed with research participants and their feedback is incorporated in the analysis. Member checking is one way of achieving transactional validity, which has been heralded as a stronger version of validity reached through triangulation. Through member checking, we engaged with participants to ensure mutual agreement and understanding on the accounts and analysis to be published. Attaining methodological rigor and reliability is based on shared analytical understanding between researchers and research participants. However, this shared understanding does not always materialize. Participants do not always agree with researchers or with each other. As a result, efforts to increase validity created moments of conflict and challenged epistemic authority. This article provides detailed accounts of these conflicts and challenges and their eventual, even if problematic, resolution in the context of broader approaches in participatory research. The importance of a dialogical and recursive research process with participant communities, which cannot be assumed to be homogeneous, is underscored.